Neonatal Screening and Genotype-Phenotype Correlation of 21-Hydroxylase Deficiency in the Chinese Population - Wang, Xin; Wang, Yanyun; Ma, Dingyuan; Zhang, Zhilei; Li, Yahong; Yang, Peiying; Sun, Yun; Jiang, Tao (Frontiers in Genetics, 2021)
Background: Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders encompassing enzyme deficiencies in the adrenal steroidogenesis pathway that leads to impaired cortisol biosynthesis. 21-hydroxylase deficiency (21-OHD) is the most common type of CAH. Severe cases of 21-OHD may result in death during the neonatal or infancy periods or sterility in later life. The early detection and timely treatment of 21-OHD are essential. This study aimed to summarize the clinical and genotype characteristics of 21-OHD patients detected by neonatal screening in Nanjing, Jiangsu province of China from 2000 to 2019. Methods: Through a retrospective analysis of medical records, the clinical presentations, laboratory data, and molecular characteristics of 21-OHD patients detected by neonatal screening were evaluated. Results: Of the 1,211,322 newborns who were screened, 62 cases were diagnosed with 21-OHD with an incidence of 1:19858. 58 patients were identified with the classical salt-wasting type (SW) 21-OHD and 4 patients were identified with simple virilizing type (SV) 21-OHD. Amongst these patients, 19 cases patients accepted genetic analysis, and another 40 cases were received from other cities in Eastern China. 18 different variants were found in the CYP21A2 gene. The most frequent variants was c.293-13A/C>G (36.29%). The most severe clinical manifestations were caused by large deletions or conversions of CYP21A2. Conclusions: This study suggested that neonatal screening effectively leads to the early diagnosis of 21-OHD and reduces fatal adrenal crisis. Our data provide additional information on the occurrence and genotype-phenotype correlation of 21-OHD in the Chinese population which can be used to better inform treatment and improve prognosis.